Legal Aspects Of Prima Ternate Hospital Waste Management For Environmental Pollution Prevention - Rusdin Alauddin; irham Rosyidi; Wahda Zainal Imam (Law and Justice, 2022)
Introduction: Hospitals have an important role in providing health services to the community and recovery for patients. Besides positive hospital activities, there are also hospital activities that have negative consequences such as producing medical waste and non-medical waste. Methods: The research method used is empirical legal research by conducting observations and interviews in the field Garbage or hospital waste is considered to be a link in the spread of infectious diseases. Result: Waste can cause health problems, injury and environmental pollution because it contains toxic chemicals and sharp objects. Discussion: This study aims to analyze and evaluate waste management at Prima Ternate Hospital in the context of preventing environmental pollution. showed that the greater the waste generated by Prima Ternate Hospital, the greater the potential to pollute the environment. Consclussion: Therefore, the implementation of good hospital waste management is very necessary to get a hospital condition that meets environmental health requirements.